Inventory Management Applications for Healthcare Supply Chains - Laquanda Leaven; Kamal Ahmmad; Demesha Peebles (International Journal of Supply Chain Management, 2017)
Recently, the healthcare industry has started using inventory management applications to achieve efficiency and effectiveness in its supply chains. There is a rapid growth in the demand of drugs and diagnostic systems within the healthcare industry. The biggest challenge for health care supply chains is to manage inventory efficiently and keep up the satisfactory service level at the same time. In order to meet the increased demand of healthcare products, healthcare supply chain professionals must find efficient and effective ways to improve and optimize inventory. Moreover, perishability and disposability of many medical products have been major problems in healthcare supply chain management. The current managerial practices and conflicts among different stakeholders in health care supply chains are directly associated with the issue of inventory management. This literature review will introduce various inventory management applications that are mainly focused on minimizing inventory costs and increasing overall efficiency in healthcare supply chains. The uses of simulation, new technologies to track healthcare products, new managerial practices, optimization, and information sharing techniques have been discussed throughout this literature review. We have also discussed pharmaceutical inventory management strategies in great detail, as pharmaceuticals are one of the main products of healthcare supply chains.